Optimizing Forest Resources for Sustainable Livestock Farming in Besowo Natural Reserve Buffer Zone, Indonesia - Ramadhan, Ahmad Maulana Widhi; Azizah, Siti; Baig, Mirza Barjees; Aprylasari, Dede (CV. Komunitas Dunia Peternakan, 2025)
Livestock farmers in Besowo Village, a buffer zone of the Besowo Natural Reserve, rely heavily on forest resources, leading to potential environmental and social challenges. This study, conducted from August to October 2023 in Kediri Regency, Indonesia, employs a quantitative descriptive survey method with data collected through observations, interviews, questionnaires, and documentation. Data analysis was performed using SWOT and QSPM to identify sustainable forest resource utilization strategies for livestock farming. Farmers utilize non-timber forest products, including Pennisetum purpureum, Pennisetum purpureum cv. Mott, various weeds, and tree leaves such as Swietenia mahagoni, sengon (Albizia chinensis), and mindi (Melia azedarach) for livestock feed. Timber forest products like Swietenia mahagoni, sengon, gembilina (Gmelina arborea), balsa (Ochroma grandiflorum), and salam (Syzygium polyanthum) are used for firewood and livestock pens. The SWOT analysis recommends sustainable strategies, including monitoring forest resource use, optimizing sharecropping land for forage planting, empowering farmers through conservation programs, and enhancing goat and sheep farming. The QSPM analysis emphasizes the importance of government and Perhutani support in ensuring sustainable forest resource utilization. Strengthening institutional collaboration and promoting agroforestry-based livestock farming could further enhance sustainability and reduce dependence on forest resources.